Targeting Groups Employed in Selective Dendrons and Dendrimers - Rodrigo Vieira Gonzaga; Soraya da Silva Santos; Joao Vitor da Silva; Diego Campos Prieto; Debora Feliciano Savino; Jeanine Giarolla; Elizabeth Igne Ferreira (MDPI AG, 2018)
The design of compounds with directed action to a defined organ or tissue is a very promising approach, since it can decrease considerably the toxicity of the drug/bioactive compound. For this reason, this kind of strategy has been greatly important in the scientific community. Dendrimers, on the other hand, comprise extremely organized macromolecules with many peripheral functionalities, stepwise controlled synthesis, and defined size. These nanocomposites present several biological applications, demonstrating their efficiency to act in the pharmaceutical field. Considering that, the main purpose of this review was describing the potential of dendrons and dendrimers as drug targeting, applying different targeting groups. This application has been demonstrated through interesting examples from the literature considering the last ten years of publications.